Spherical powder for making three-dimensional objects
By using refractory metal spherical alloy powder, combined with cold isostatic pressure and electrode induction melting process, the problems of powder inequality and insufficient mechanical properties in the prior art are solved, and the production of non-porous mechanical stable components in high-temperature applications is realized. Improved density and performance.
Patent Information
- Application Number
- CN202080079042.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-15
- Filing Date
- 2020-11-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-11-13
AI Technical Summary
The prior art is prone to introducing foreign particles and impurities when producing alloy powders, resulting in uneven microstructure of the powder, affecting the mechanical properties and stability of the components, especially in high-temperature applications, there are problems of insufficient porosity and mechanical strength.
Using spherical alloy powder composed of at least two refractory metals, produced by cold isostatic pressure and electrode induction melting processes to ensure that the powder has a uniform microstructure and at least two different crystal phases, improves fluidity and sintering activity, and is suitable for In additive manufacturing and injection molding.
It realizes poreless and mechanically stable three-dimensional component production, especially suitable for high-temperature applications, improves the density and mechanical properties of the components, and reduces energy consumption and oxygen absorption during the production process.
Smart Images

Figure CN114641357B_ABST
Abstract
Description
[0001] The present invention relates to a spherical alloy powder composed of at least two refractory metals, wherein the alloy powder has a uniform microstructure and at least two different crystalline phases, and to a method for producing such a powder. The present invention also relates to the use of such a powder in the manufacture of three-dimensional components and components produced from such a powder.
[0002] There are various methods for producing metal parts with complex geometries. On the one hand, such parts can be produced with the aid of additive manufacturing (also known by the abbreviation 3D printing). The term "additive manufacturing" includes all manufacturing methods that produce three-dimensional objects by applying materials layer by layer under computer control and connecting the layers to each other usually by physical and chemical solidification processes or melting processes. Additive manufacturing methods are characterized in particular by their high precision and shape accuracy and can produce models and patterns quickly and cost-effectively. Another possibility for producing metal parts is metal injection molding (MIM), which originated from the injection molding technology of plastics. In MIM, fine metal powder is mixed with an organic binder and introduced into a mold with the aid of an injection molding machine. The binder is then removed and the component is sintered. In this way, the mechanical advantages of the sintered component can be combined with the large molding variety of injection molding. As a further advantage, this method offers the possibility of producing components with very demanding geometries in a single piece, which can only be produced in several parts using conventional methods.
[0003] Common materials used in additive manufacturing and injection molding are polymers, synthetic resins, ceramics and metals. Although there is now a large selection of plastic materials that are routinely used in these processes, there is still a demand for suitable powders in the metal sector, which must especially have good flowability and high sintering activity in order to be able to be processed into stable and durable objects.
[0004] WO 2011 / 070475 describes a method for producing an alloy of at least two high-melting-point metals, wherein according to the method the two high-melting-point metals are melted and mixed in a melting crucible using an electron beam, and the melt is solidified, wherein the molten metals are heated at 200 Ks -1 Up to 2000 Ks -1 The solidification is carried out by quenching at a cooling rate within a range of 100 to 200 °C. It is recommended to provide the two metals in powder form and to mix them with each other before melting so that the two metals are completely dissolved in each other. It is particularly important here that the two metals form a solid solution in any combination and prevent the appearance of second phases. However, the method described has the disadvantage that a large amount of impurities are introduced into the powder by the use of a melting crucible and the high temperatures required.
[0005] US 2019 / 084048 discloses a method for producing atomized spherical β-Ti / Ta alloy powder for additive manufacturing, comprising the following steps: a) mixing elemental Ti and Ta powders to form a Ti-Ta powder composition; b) hot isostatic pressing the powder composition to form a Ti- / Ta electrode and c) treating the Ti / Ta electrode by means of EIGA to obtain an atomized spherical Ti / Ta alloy powder. However, a disadvantage of the method is that the resulting powder has an inhomogeneous microstructure, which may be undesirable for certain applications.
[0006] CN 108296490 provides a method for producing spherical tungsten-tantalum alloy powder, wherein irregularly shaped tungsten-tantalum mixed powder is used as raw material and the tungsten-tantalum mixed powder is produced by high-energy ball milling. The raw material powder used is formed into the desired alloy powder by means of plasma spheroidization. As is known to all, the grinding method used has the disadvantage of undesirably introducing wear material from the grinding balls.
[0007] Disadvantages of the methods described in the prior art for producing alloy powders are that sometimes a large proportion of foreign particles is introduced into the powder during the production process and that the powder has a dendritic element distribution, which in turn has an adverse effect on the quality of the components produced from the powder, since these components must be sintered for a relatively long time and generally also at a relatively high temperature in order to obtain the required mechanical strength. The object of the present invention is therefore to overcome the disadvantages of the prior art and to provide a powder which enables the production of nonporous and mechanically stable components suitable for high-temperature applications, in particular components with complex geometries.
[0008] Surprisingly, it has been found that this object is achieved by a powder which consists of an alloy of at least two refractory metals and has a homogeneous microstructure and at least two different crystal phases.
[0009] Thus, a first subject of the present invention is a spherical powder for producing three-dimensional parts, wherein the powder is an alloy powder composed of at least two refractory metals, wherein the alloy powder has a homogeneous microstructure and at least two different crystalline phases.
[0010] The powder according to the invention is characterized by good flowability and high sintering activity, which enables the production of pore-free and mechanically stable components by means of additive manufacturing and / or injection molding.
[0011] Within the scope of the present invention, the expression "alloy powder" is to be regarded as synonymous with the powder of the present invention, unless otherwise specified.
[0012] Refractory metals in the sense of the present invention are high-melting base metals of the third, fourth, fifth and sixth subgroups of the periodic table of the elements. These metals are characterized, in addition to their high melting point, in that they have a passivation layer at room temperature.
[0013] In the context of the present invention, the term "alloy powder" refers to a powder in which a refractory metal is present in alloy form and forms a macroscopically uniform powder. These powders are different from mixed powders in which a plurality of components are present separately in the form of a mixture and there is a macroscopically non-uniform element distribution.
[0014] A “homogeneous microstructure” in the sense of the present invention is understood to mean a homogeneous element distribution, ie a homogeneous distribution and spatial filling of the alloy components in the individual powder particles without macroscopic fluctuations here and there.
[0015] In the context of this application, the term particle size refers to the longest linear dimension of a powder particle from one end of the particle to the opposite end.
[0016] Agglomerates in the sense of the present invention are understood to mean solidified accumulations of previously loose powder particles. Previously loose particles that form agglomerates, for example by means of sintering, are referred to as primary particles.
[0017] Additive manufacturing and MIM are being used in almost all industrial sectors. The properties of the produced components can be influenced by the powder used, and in addition to the mechanical properties of the component, other properties such as optical and electronic properties can also be adjusted.
[0018] Therefore, an embodiment of the powder according to the invention is preferred, in which the refractory metal is a refractory metal selected from tantalum, niobium, vanadium, yttrium, titanium, zirconium, hafnium, tungsten and molybdenum. In a particularly preferred embodiment, at least two refractory metals are tantalum and tungsten. In a particularly preferred embodiment, the alloy powder according to the invention does not contain Ti. In this case, it is particularly preferred that the proportion of titanium in the alloy powder according to the invention is less than 1.5% by weight, particularly preferably less than 1.0% by weight, in particular less than 0.5% by weight, especially less than 0.1% by weight, in each case based on the total weight of the alloy powder.
[0019] The powder of the present invention is characterized in that the alloy powder has at least two different crystalline phases. It has been found that it is particularly advantageous when one of these crystalline phases is a metastable crystalline phase. In this article, a metastable crystalline phase is understood to refer to a phase that is thermodynamically unstable at room temperature. The crystalline phases that appear in the alloy powder of the present invention can be determined, for example, by means of X-ray diffraction analysis (RBA) and can be distinguished by means of their reflections in the X-ray diffraction pattern. The distribution of different crystalline phases in the powder can vary. A preferred embodiment of the present invention is characterized in that one crystalline phase accounts for a larger proportion than other crystalline phases. The phase with the largest proportion is referred to as the main crystalline phase, and the phase with a smaller proportion is referred to as the secondary crystalline phase or secondary phase. The powder of the present invention preferably has a main crystalline phase and at least one secondary crystalline phase. Surprisingly, it has been found that the ratio of the phases affects the mechanical properties of the subsequent components, wherein the ratio of the phases can be determined by means of their reflection intensity in the X-ray diffraction pattern (given as pulses [°2θ] per angle there). In a particularly preferred embodiment, the ratio of the reflection with maximum intensity of at least one secondary phase (I(P2)100) to the reflection with maximum intensity of the main crystalline phase (I(P1)100), expressed as I(P2)100 / I(P1)100, is preferably less than 0.75, particularly preferably 0.05 to 0.55, in particular 0.07 to 0.4, in each case determined by means of X-ray diffraction.
[0020] Another characteristic of the powder according to the invention is its homogeneous microstructure. In general, alloy powders, in particular alloy powders of refractory metals, have the disadvantage that, due to production, the different alloy components are not evenly distributed in the individual powder particles, because the residence time of the particles is usually too short to achieve a thorough mixing and diffusion of the individual components. This uneven distribution leads in particular to disadvantages in the mechanical properties of the components themselves made from these powders, which can only be compensated by using significantly higher energy inputs during production, for example by significantly higher laser powers or lower laser scanning speeds in the SLM method. However, surprisingly, it has been found within the scope of the present invention that the powder itself already has a homogeneous distribution of the alloy components. Therefore, an embodiment of the powder according to the invention is preferred, in which at least 95%, preferably at least 97%, particularly preferably at least 99% of all powder particles, the variation in the content of alloy elements expressed in weight % within the particles is less than 8%, preferably 0.05 to 6%, particularly preferably 0.05 to 3%, determined by means of EDX (energy dispersive X-ray spectroscopy).
[0021] The powder of the invention is characterized in particular by its spherical shape, which makes it particularly suitable for additive manufacturing and injection molding. Therefore, preferred embodiments are those in which the powder particles have an average aspect ratio Ψ of 0.7 to 1, preferably 0.8 to 1, particularly preferably 0.9 to 1, in particular 0.95 to 1 A , where ΨA Defined as the ratio of the minimum Feret diameter to the maximum Feret diameter, denoted as Ψ A = x Feret min / x Feret max Here, the Feret diameter is the distance between two tangent lines of a particle at any angle. The maximum Feret diameter x Feret max90 This can be done by first determining the maximum Feret diameter and then determining the Feret diameter offset by 90° relative to the maximum Feret diameter. This applies analogously to determining the minimum Feret diameter. For example, the Feret diameter of a particle can be determined by image evaluation of scanning electron micrographs (REM photographs) (see also FIG. 9 for this).
[0022] In addition to sphericity, the flowability of a powder is another criterion that determines its suitability, in particular for additive manufacturing methods. The powders according to the invention are characterized by a flowability that matches the requirements in these manufacturing processes. An embodiment of the powder according to the invention is therefore preferred, in which the powder has a flowability of less than 25 s / 50 g, preferably less than 20 s / 50 g, in particular less than 15 s / 50 g, in each case determined according to ASTM B213.
[0023] Furthermore, the powders according to the invention are characterized by a high tap density, which is another criterion to be considered when selecting a powder for such a manufacturing process. In a preferred embodiment, the powders according to the invention have a tap density of 40 to 80% of their theoretical density, preferably 60 to 80% of their theoretical density, in each case determined according to ASTM B527.
[0024] It is known that the mechanical properties and porosity of the components produced by means of such a production method can be controlled in particular by the particle size of the powder used, wherein the particle size should be selected according to the respective production method, wherein in particular a narrow particle size distribution has proven to be advantageous. In a preferred embodiment of the invention, the particle size distribution of the powder according to the invention is a D10 value of more than 2 μm, preferably more than 5 μm, and a D90 value of less than 80 μm, preferably less than 70 μm, wherein the D50 value is 20 to 50 μm, preferably 25 to 50 μm, in each case determined according to ASTM B822. This particle size distribution has proven to be particularly advantageous for the selective laser melting (SLM) method.
[0025] In a further preferred embodiment, the powder according to the invention has a particle size distribution with a D10 value of greater than 20 μm, preferably greater than 50 μm, and a D90 value of less than 150 μm, preferably less than 120 μm, wherein the D50 value is from 40 to 90 μm, preferably from 60 to 85 μm, in each case determined according to ASTM B 822. In particular in the field of electron beam melting (EBM), a particle size distribution as given has proven to be particularly advantageous.
[0026] In another preferred embodiment, the powder according to the invention has a particle size distribution with a D10 value of more than 50 μm, preferably more than 80 μm and a D90 value of less than 240 μm, preferably less than 210 μm, wherein the D50 value is from 60 to 150 μm, preferably from 100 to 150 μm, in each case determined according to ASTM B 822. Powders with such a particle size distribution have proven to be particularly advantageous when using the laser cladding method (CL).
[0027] In another preferred embodiment, the powder according to the invention has a particle size distribution with a D10 value of greater than 1 μm, preferably greater than 2 μm and a D90 value of less than 45 μm, preferably less than 40 μm, wherein the D50 value is 6 to 30 μm, preferably 8 to 20 μm, in each case determined according to ASTM B 822. In particular, when such powders are used for injection molding processes such as metal injection molding (MIM), a particle size distribution in the ranges specified has proven to be advantageous.
[0028] Within the scope of the present invention, the D50 value is understood to be the average particle size at which 50% of the particles are smaller than the stated value. The same applies analogously to the D10, D90 and D99 values.
[0029] Another subject of the present invention is a method for producing the alloy powder of the present invention. The method of the present invention comprises the following steps:
[0030] a) providing a starting powder mixture comprising at least two refractory metals, wherein the starting powder mixture has a particle size with a D99 value of less than 100 μm and at least one refractory metal has a particle size with a D99 value of less than 10 μm, in each case determined according to ASTM B822;
[0031] b) producing a powder body from the starting powder mixture by means of cold isostatic pressing (CIP);
[0032] c) sintering the compact at a temperature of 400 to 1150° C. below the lowest melting point of the components of the starting powder mixture, preferably below 700 to 1050° C.;
[0033] d) melting the sintered body by means of electrode induction melting (EIGA); and
[0034] e) Atomizing the melt and cooling it simultaneously to obtain spherical alloy powder.
[0035] Surprisingly, it has been found that by the process of the invention a spherical powder with a narrow particle size distribution and a high sintering activity is obtained, which allows the production of non-porous and mechanically stable components by means of additive manufacturing or MIM. The powder produced by the process of the invention is also characterized by a homogeneous distribution of the alloying components and the presence of at least two crystalline phases.
[0036] The pressing of the powder (CIP) is preferably carried out at an applied pressure of at least 1.7·10 8 Pa (1700 bar), particularly preferably at least 1.9·10 8 The pressing pressure was 1900 bar (1900 m).
[0037] In a preferred embodiment, the method of the invention further comprises a classification step, preferably sieving. In this way, the desired particle size distribution can be matched and set.
[0038] In a further preferred embodiment, the starting powder mixture has a particle size with a D99 value of less than 100 μm, preferably less than 80 μm, determined in each case by means of ASTM B822.
[0039] In a preferred embodiment, at least one refractory metal in the starting powder mixture has a particle size with a D99 value of less than 10 μm, preferably less than 5 μm, particularly preferably less than 2 μm, in each case determined with the aid of ASTM B822, wherein the refractory metal is preferably the refractory metal with the highest melting point.
[0040] It has proven to be advantageous to use refractory metals whose primary particles have been sintered to form porous agglomerates in the starting powder mixture, in particular those refractory metals whose primary particle size is less than 10 μm, preferably less than 3 μm, particularly preferably less than 1 μm, as determined by image evaluation of scanning electron micrographs (REM photographs). Therefore, an embodiment is preferred in which at least one refractory metal of the starting powder mixture is present in the form of sintered porous agglomerates having a particle size of less than 100 μm, preferably less than 80 μm, as determined in accordance with ASTM B822, and which have a primary particle size of less than 10 μm, preferably less than 3 μm, particularly preferably less than 1 μm, as determined by REM photographs.
[0041] The sintering in step c) of the method of the invention is carried out at a temperature of 400 to 1150° C., preferably 700 to 1050° C., below the melting point of the alloy component with the lowest melting point, wherein the melting points of the alloy components are known to those skilled in the art or can be obtained from the literature. The duration of the sintering process can be adjusted according to the desired powder properties, but is preferably 0.5 to 6 hours, particularly preferably 1 to 5 hours.
[0042] In the context of the present invention, it is preferred to use refractory metals having a high melting point. Sintering is therefore preferably carried out at a temperature of at least 1400°C.
[0043] It has been shown that for certain applications, a high oxygen content in the alloy powder has a negative effect on its use in certain production methods. Therefore, an embodiment of the method according to the invention is preferred in which the alloy powder is further subjected to a deoxidation step in the presence of a reducing agent, preferably magnesium or calcium being used as the reducing agent, in particular in the form of vapor. A person skilled in the art can find a detailed description of suitable deoxidation processes, for example, in the patent document EP 1 144 147.
[0044] In order to keep the oxygen content of the powder according to the invention as low as possible already during the production process, it has proven to be advantageous to carry out the cooling in an oxygen-depleted environment. Therefore, preference is given to an embodiment in which the cooling is carried out during the atomization by means of a cooled inert gas.
[0045] However, for specific applications, the oxygen content needs to be adjusted in a targeted manner. Therefore, in a preferred embodiment, an oxygen-containing component of the refractory metal, such as its oxide or suboxide, is added to the starting powder mixture in order to adjust the desired oxygen content in the powder according to the invention in a targeted manner.
[0046] Surprisingly, it has been shown that the powder according to the invention can be used not only for additive manufacturing methods, but also for producing three-dimensional components by means of metal injection molding (MIM). Therefore, another subject of the present invention is the use of the powder according to the invention or the powder obtained according to the method according to the invention in additive manufacturing methods and / or metal injection molding methods. The additive manufacturing method is preferably one selected from the group consisting of selective laser melting (SLM), electron beam melting (EBM) and laser cladding (LC).
[0047] Another subject of the invention is a component produced using the alloy powder of the invention or the powder obtained by means of the method of the invention. Preferably, the component is a component used in high-temperature applications, for example in the range of drive mechanisms and high-temperature furnaces. Alternatively, the component is preferably a medical implant or an appliance.
[0048] Example:
[0049] The invention is explained in more detail with the aid of the following examples, wherein these examples are in no way to be understood as limiting the inventive concept.
[0050] Powders Ta2.5W (E1) and Ta13W (E2) according to the invention were produced; in which the particle size D99 of the tantalum powder used in the starting powder mixture was 49 μm and the particle size D99 of the tungsten powder was 1.9 μm, in each case measured according to ASTM B822. The powders were formed into pressed bodies by means of cold isostatic pressing (CIP) at a pressing pressure of 2000 bar, which were sintered at 1950° C. for two hours. The sintered bodies thus obtained were melted by means of electrode induction melting (EIGA) and the melt was atomized while cooling. After the atomized powder was classified into two fractions (<63 μm, 63-100 μm) by sieving, the resulting alloy powder <63 μm was deoxidized in the presence of Mg at 1000° C. for 2 hours. The composition and properties of the powders obtained are summarized in Table 1, where the respective parameters have been determined according to the criteria given above.
[0051] The oxygen and nitrogen contents of the powders were determined by means of carrier gas hot extraction (Leco TCH600), the particle size was determined in each case by means of laser scattering (ASTM B822, MasterSizer S, dispersion in water and Daxad 11.5 min ultrasound treatment). Trace analysis of metallic impurities was carried out by means of ICP-OES with the following analytical instruments PQ 9000 (AnalytikJena) or Ultima 2 (Horiba). The determination of the crystalline phase was carried out with an instrument from Malvern-PANalytical (X´Pert-MPD with semiconductor detector, X-ray tube Cu LFF, 40 kV / 40 mA, Ni-filter).
[0052] Table 1:
[0053]
[0054]
[0055] In the powders according to the invention, two different crystalline phases can be identified in the X-ray diffraction pattern, a cubic main phase and a tetragonal secondary phase, as can also be seen in Figures 1 and 2, which show photographs of the powders according to the invention Ta2.5W (Figure 1) and Ta13W (Figure 2), respectively. The ratios of the reflection intensities of the reflections with the respective maximum intensity obtained are given in Table 1.
[0056] Further photographs of powdered Ta13W from experiment E2b show that, unlike conventional powders, no dendritic structure is visible and the powder particles are spherical. Here, Figure 3 shows an EDX photograph of a polished sample of powdered Ta13W, while Figure 4 The REM images with the aid of scattering slices show the spherical shape of the Tal3W powder particles.
[0057] For comparison purposes, powdered Ta2.5W (Comparison 1) was produced according to a conventional process, wherein an ingot was first produced by means of an electron beam. It was embrittled by hydriding with hydrogen and ground. The hydrogen was removed in a high vacuum and the material was sieved to a value of less than 63 µm. The corresponding results are summarized in Table 2.
[0058] As shown by X-ray diffraction analysis and REM images, the obtained powders had neither two distinct crystalline phases nor a spherical morphology (see Figures 5a and 5b).
[0059] Table 2:
[0060]
[0061] As a further comparison, powder Ta2.5W (Comparison 2) was prepared, in which the corresponding starting powder was pressed and sintered at 1200°C to form a metal body, which was subsequently atomized. The particle sizes D99 of the starting metals Ta and W were 150 μm and 125 μm. The results are likewise summarized in Table 2.
[0062] A third comparative powder was prepared analogously to comparative 2, but in which 13 wt.% W was used (Comparative 3, see Table 2).
[0063] like Figure 6a It is clear that the powder of comparison 3 has a dendritic microstructure; the variation of the tantalum and tungsten content is represented by different grayscale levels and is up to 15% by weight in the region marked with 1 to 4. No second crystalline phase can be identified (see Figure 6b ).
[0064] As shown by the comparative experiments, it is not possible to obtain a powder with a homogeneous microstructure or element distribution and simultaneously with two different crystalline phases using the known methods.
[0065] The powder of comparison 3 (comparison 3) and the powder E2b according to the invention were printed by means of SLM with the printing parameters given in Table 3. The aim was to produce a cubic component with an edge length of about 2.5 cm and a homogeneous microstructure that was as dense as possible. The density of the component is given in % as the ratio of the actually measured component density to the theoretical density of the alloy. A density of less than 100% indicates the presence of undesired pores that could have a negative impact on the mechanical properties of the component.
[0066] Components produced with the powder according to the invention can already be obtained with the desired density at low laser powers or volume energy densities, which results in, among other things, increased process reliability, lower energy consumption and lower oxygen absorption by the residual powder. Alternatively, the scanning speed of the laser can be increased, thereby achieving higher production throughputs.
[0067] Table 3:
[0068] SLM printing experiment D1 D2 D3 D4 The TaW alloy powder used was obtained from the experiment Comparison 3b Comparison 3b E2B E2B SLM printing parameters Laser scanning speed [mm / s] 900 900 900 1300 Laser power[W] 110 170 110 170 Volume energy density [J / mm3] 76 118 76 81 Crystal phase after printing cube cube cube cube Microstructure determined by EDX Uniform Uniform Uniform Uniform Variation of alloying elements within powder particles, weight % 7.2 5.1 3.8 4 Actual density of the printed body relative to the theoretical density of the alloy [%] 79.5 99.2 99 99.3
[0069] Figure 7 An REM photograph of a ground sample of a component (D3) produced with powder E2b according to the invention is shown, the density of which is 99% of the theoretical density.
[0070] Figure 8 The REM photograph of a ground sample of part D1 produced with comparative powder Comparative 3b is shown. The low density of this part, which is less than 80% of the theoretical density, can be clearly seen.
Claims
1. Spherical alloy powder for manufacturing three-dimensional parts, characterized in that The spherical alloy powder is a spherical alloy powder composed of at least two refractory metals, wherein the spherical alloy powder has a uniform microstructure and at least two crystal phases, wherein the refractory metal is tantalum, niobium, vanadium, yttrium, titanium, zirconium, hafnium, tungsten and molybdenum, wherein the spherical alloy powder has a main crystalline phase and at least one secondary crystalline phase, wherein the ratio of the reflection intensity obtained from the X-ray diffraction pattern having the maximum intensity (I(P2)100) of the at least one secondary crystalline phase and the maximum intensity (I(P1)100) of the main crystalline phase, expressed as I(P2)100 / I(P1)100, is less than 0.75, as determined by means of X-ray diffraction, wherein in at least 95% of all spherical alloy powder particles, the content of alloying elements expressed in weight % within the particle varies by less than 8%, as determined by means of EDX, i.e. energy dispersive X-ray spectroscopy; and The fluidity of the spherical alloy powder is less than 25s / 50g, measured according to ASTM B213.
2. The spherical alloy powder according to claim 1, characterized in that The refractory metals are tungsten and molybdenum.
3. The spherical alloy powder according to claim 1 or 2, characterized in that: The spherical alloy powder is substantially free of Ti, wherein the Ti content in the spherical alloy powder is less than 1.5 wt %. 4 . The spherical alloy powder according to claim 3 , wherein the Ti content in the spherical alloy powder is less than 1.0 wt %. 5 . The spherical alloy powder according to claim 3 , wherein the Ti content in the spherical alloy powder is less than 0.5 wt %. 6 . The spherical alloy powder according to claim 3 , wherein the Ti content in the spherical alloy powder is less than 0.1 wt %.
7. The spherical alloy powder according to claim 1 or 2, characterized in that: One of the crystal phases is a metastable crystal phase.
8. Spherical alloy powder according to claim 1 or 2, wherein the ratio of the reflection intensities resulting from an X-ray diffraction pattern having a maximum intensity of at least one secondary crystalline phase (I(P2)100) and a maximum intensity of a primary crystalline phase (I(P1)100), expressed as I(P2)100 / I(P1)100, is from 0.05 to 0.55, in each case determined by means of X-ray diffraction.
9. The spherical alloy powder according to claim 8, wherein the ratio of the reflection intensities from an X-ray diffraction pattern having a maximum intensity of at least one secondary crystalline phase (I(P2)100) and a maximum intensity of a primary crystalline phase (I(P1)100), expressed as I(P2)100 / I(P1)100, is from 0.07 to 0.4, in each case determined by means of X-ray diffraction.
10. The spherical alloy powder according to claim 1, wherein in at least 97% of all spherical alloy powder particles, the content of alloying elements expressed as % by weight within the particle varies by less than 8%, as determined by means of EDX, i.e. Energy Dispersive X-ray Spectroscopy.
11. The spherical alloy powder according to claim 10, wherein in at least 99% of all spherical alloy powder particles, the content of alloying elements expressed in weight % within the particle varies by less than 8%, as determined by means of EDX, i.e. Energy Dispersive X-ray Spectroscopy.
12. The spherical alloy powder according to any one of claims 1, 10 and 11, wherein the content of the alloying elements expressed as % by weight within the particles varies from 0.05 to 6%.
13. The spherical alloy powder according to any one of claims 1, 10 and 11, wherein the variation in the content of the alloying elements expressed as % by weight within the particles is from 0.05 to 3%.
14. Spherical alloy powder according to claim 1 or 2, wherein the flowability of the spherical alloy powder is less than 20 s / 50 g, in each case determined according to ASTM B213.
15. Spherical alloy powder according to claim 14, wherein the flowability of the spherical alloy powder is less than 15 s / 50 g, in each case determined according to ASTM B213.
16. The spherical alloy powder according to claim 1 or 2, characterized in that: The tap density of the spherical alloy powder is from 40 to 80% of its theoretical density, determined in each case in accordance with ASTM B527.
17. The spherical alloy powder according to claim 16, wherein the spherical alloy powder has a tap density of 60 to 80% of its theoretical density, in each case determined according to ASTM B527.
18. Process for producing a spherical alloy powder according to any one of claims 1 to 17, comprising the following steps a) providing a starting powder mixture comprising at least two refractory metals, wherein the starting powder mixture has a particle size with a D99 value of less than 100 μm and at least one refractory metal has a particle size with a D99 value of less than 10 μm, in each case determined according to ASTM B822; b) producing a powder body from the starting powder mixture by means of cold isostatic pressing (CIP); c) sintering the compact at a temperature of 400 to 1150° C. below the lowest melting point of the refractory metal of the starting powder mixture; d) melting the pressed powder body by means of electrode induction melting; and e) Atomizing the melt and cooling it to obtain spherical alloy powder.
19. The method according to claim 18, wherein in step c) the compact is sintered at a temperature of 700 to 1050°C below the lowest melting point of the refractory metal of the starting powder mixture.
20. The method according to claim 18 or 19, characterized in that One of the refractory metals in the starting powder mixture is present in the form of porous agglomerates having a particle size D99 of less than 100 μm, as determined according to ASTM B822.
21. The method according to claim 18 or 19, characterized in that Sintering is carried out for a duration of 0.5 to 6 hours.
22. The method according to claim 21, wherein sintering is carried out for a duration of 1 to 5 hours.
23. The method according to claim 18 or 19, characterized in that The spherical alloy powder is furthermore subjected to a deoxidation step in the presence of a reducing agent.
24. The method of claim 23, wherein the reducing agent is magnesium or calcium.
25. The method of claim 24, wherein the reducing agent is in the form of a vapor.
26. The method according to claim 18 or 19, characterized in that Cooling during atomization is carried out with the aid of cooled inert gas.
27. Use of a spherical alloy powder according to any one of claims 1 to 17 or a spherical alloy powder obtainable by a method according to any one of claims 18 to 26 in additive manufacturing and / or metal injection molding (MIM).
28. The use according to claim 27, characterized in that The additive manufacturing method is a method selected from the group consisting of selective laser melting (SLM), electron beam melting (EBM) and laser cladding (LC).
29. A component produced using a spherical alloy powder according to any one of claims 1 to 17 or a spherical alloy powder obtainable by a method according to any one of claims 18 to 26.
Citation Information
Patent Citations
Metal powders produced by the reduction of the oxides with gaseous magnesium
EP1144147A1
Alloy comprising two refractory metals, particularly w and ta and x-ray anode comprising such alloy and method for producing same.
WO2011070475A1
Titanium-tantalum powders for additive manufacturing
US20190084048A1
